Kontribusi Regulasi Emosi Orang Tua Terhadap Regulasi Diri Remaja melalui Peran Mediasi Pola Asuh Orang Tua - Gistilisanda Fauzin Hundra; Eva Septiana (Fakultas Psikologi Universitas Tarumanagara, 2020)
The results of the KPAI survey from 2011 to 2016 included 12,202 cases of Indonesian children and adolescents involved in risk behaviour. Jabodetabek is the area with the most cases of children and adolescents involved in risk behaviour, namely 5,160 cases. Adolescent self-regulation becomes a protective factor against risk behaviour. Parenting and parents' emotional regulation abilities become the main protective factors towards adolescent risk behaviours and adolescent self-regulation abilities. Based on that explanation, this study aims to examine the mediating role of parenting towards the contribution of parents' emotional regulation strategies to adolescent self-regulation. Data analysis of this study used multiple regression with the Hayes template model, namely model four with using one mediator variable. The sample of this study consisted of 157 pairs of study participants namely fathers, mothers, and adolescents obtained from 73 Tebet Middle School, 3 Bogor High School, and Depok 8 Middle School by using accidental sampling method. There are three measuring instruments in this study, namely The Adolescent Self-Regulatory Inventory (ASRI) to measure teenage participant self-regulation, Emotion Regulation Questionnaire (ERQ) to measure parents' emotional regulation, and Parenting Style Four Factor Questionnaire (PSFFQ) to measure parenting. Based on the results of multiple regression analysis on adolescent participants showed that there is a mediating role of paternal authoritative parenting on contribution of the paternal emotion regulation (reappraisal and suppression) to adolescent self-regulation abilities, then there is a mediating role of maternal authoritarian parenting on contributing of maternal emotion regulation (reappraisal) to adolescent self-regulation abilities.